PARADIGMA PERUBAHAN SOSIAL PERSPEKTIF CHANGE AGENT DALAM AL-QURAN (Analisis Tematik Kisah Nabi Yusuf as) - Icol Dianto (Jurnal Sosiologi Reflektif, 2019)
Social change can be studied through the classical theory of sociology, which is known as the theory of historical circle. This theory explains that history is a recurring process.Social change is not moving along a straight line but rather it follows a circle. According to the theory, history becomes a decisive factor in the process of social change. Historical events cannot be separated from the actors of history (actor), namely the leaders that ultimately affect the course of changes that occur in society. This paper  attempts to present the study of social change perspective of history of a great man, namely the Prophet Yusuf. The success of the Prophet Yusuf inrescuing the Egyptians from the long drought deserves to be studied, both his position as the messenger of Allah and his status as a human being who has its own charm. Using the thematic interpretation method to interpret Quranic verses and fenomenological analysis methods to analyze topics related to the social phenomena contained in the story of Prophet Yusuf, this research founds that the concept of social change in the story of Yusuf lies on three aspects, namely the integrity of solid sturdiness, the concept of clear social change, and the planned process of social change. Perubahan sosial dapat dikaji melalui teori klasik sosiologi yakni teori lingkar sejarah. Teori ini menjelaskan bahwa sejarah merupakan proses yang berulang, perubahan sosial tidak bergerak menurut garis lurus melainkan melingkar. Menurut teori tersebut, sejarah menjadi faktor penentu dalam proses perubahan sosial. Peristiwa sejarah tidak dapat dipisahkan dari pelaku sejarah (actor), yakni profil orang besar yang pada akhirnya mempengaruhi jalannya perubahan-perubahan yang terjadi pada masyarakat. Dalam paper ini penulis berupaya menyajikan kajian perubahan sosial perspektif sejarah orang besar, yakni Nabi Yusuf as. Keberhasilan Nabi Yusuf as menyelamatkan rakyat Mesir dari masa kemarau yang panjang patut untuk dikaji, baik posisinya sebagai utusan Allah dan statusnya sebagai manusia biasa yang memiliki daya tarik tersendiri. Dengan menggunakan metode analisis tafsir tematik untuk menafsir ayat-ayat al-Quran dan metode analisis fenomenologi untuk menganalisis topik yang terkait dengan fenomena sosial yang ada dalam kisah Nabi Yusuf. Penulis mendapatkan konsep perubahan sosial dari kisah Yusuf as atas tiga aspek, yaitu integritas ketokohan yang mantap, konsep perubahan sosial yang jelas dan proses perubahan sosial yang terencana.